Passive victims or active agents? - Nyanzi, Stella; Walakira-Emodu, Margaret (Exchange on HIV/AIDS, Sexuality and Gender Issue, 2008)
In patriarchal cultures where women and girls are perceived as commodities belonging to the male family line, widow inheritance is widely practiced. Evidence shows that widow inheritance is common in several countries in Africa and Asia – including Ghana, Kenya, Nigeria, South Africa, Tanzania, Uganda, Zambia, Zimbabwe, India and China.1-2 Due to the diversity of cultures, there are several differences in the actual enactment of widow inheritance: the heir remarries the widow; an older brother to the deceased takes over the widow’s sexual and reproductive rights; or the widow is handed over by the clan-elders to an unmarried member of the clan
Keywords: Passive; active agents